2022
DOI: 10.3389/ffgc.2022.909901
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of landscape-scale forest loss and a dry event on the demographic structure of the endangered palm Euterpe edulis Mart. in the Atlantic Forest

Abstract: Forest loss is one of the most serious threats to biodiversity in the tropics and mainly occurs due to the conversion of native forests by the expansion of human activities. In addition, regional climate change is likely to adversely affect the remaining biota. These disturbances may have direct or indirect consequences on the demographic structure of plant species in human-modified landscapes. To test this hypothesis, and thus look for management practices aimed at enhancing the population viability, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Thus, lower density at the edges is a pattern that involves many ecological aspects, of E. edulis mortality by human pressures, such as the direct damage by harvesting or indirect damage through edge effects, pollution, loose of pollinators, fertilizers, pathogen infestation, and pesticides. Also, other studies carried out in the Atlantic Forest have shown that the forest structure that surrounds the palm populations (Leal et al, 2022) and direct damage caused by primates, especially in edge areas (Portela & Dirzo, 2020), can negatively influence the recruitment of this palm species.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, lower density at the edges is a pattern that involves many ecological aspects, of E. edulis mortality by human pressures, such as the direct damage by harvesting or indirect damage through edge effects, pollution, loose of pollinators, fertilizers, pathogen infestation, and pesticides. Also, other studies carried out in the Atlantic Forest have shown that the forest structure that surrounds the palm populations (Leal et al, 2022) and direct damage caused by primates, especially in edge areas (Portela & Dirzo, 2020), can negatively influence the recruitment of this palm species.…”
Section: Discussionmentioning
confidence: 98%
“…While these linear canopy openings may appear less harmful, especially when compared to fire-prone sites, agricultural fields (Prieto et al, 2014) and forest islands (Benchimol & Peres, 2015), they also can facilitate human impacts such as the entry of hunters and collectors. On the other hand, E. edulis has been managed for many centuries and the human intervention can be also positive through restoration, management (Leal et al, 2022) and fruit harvesting.…”
Section: Discussionmentioning
confidence: 99%